Degradation of Acetic Acid to decrease COD by Photocatalytic Process in Wastewater: TiO2 catalyst with UV Process - Mohammad Shareei; Reza Mosayebi Behbahani; Fatemeh Rashedi (Iranian Journal of Chemical Engineering)
This study was conducted to decrease the concentration of acetic acid in wastewater of acetic acid plants through the photocatalytic oxidation method. This process employed commercial Titanium dioxide powder (TiO2) as a photocatalyst, utilizing a UV lamp as the light source within a batch reactor system for advanced oxidation. Various experimental parameters were modified, including the concentration of acetic acid, the amount of catalyst, the volume of waste, temperature, and reaction time. The residual acid concentration and COD values were recorded as results of the process. The percentage of acetic acid remaining in the solution was determined by using a gas chromatography (G.C) device. Experiments were conducted with different volumes, from 200 ml to 35 ml, and utilized varying amounts of photocatalyst: 0.01 g, 0.005 g, 0.0025 g, and 0.001 g. Additionally, the experiments were carried out over two-time intervals of 2 hours and 5 hours. The wastewater concentration contained 3% by mass of acetic acid, and the average COD value was 13300. After experiments, it was found that the optimal conditions for removing acetic acid were a volume of 35 ml and 0.0025 g of catalyst used for 2 hours. In this condition, the percentage of acetic acid decreased from 3% to 0.2%, which is a 93% decrease, and the COD decreased from 13,300 to 2,800, which is a 79% decrease.